Recent Advances in the Cross-Coupling of Arylaluminums with Electrophile Reagents - Qinghan, Li; Xin, Jiang; Kun, Wu; Ruiqiang, Luo; Zhihao, Zhang; Meng, Liang; Zheyao, Huang (Mini-Reviews in Organic Chemistry, 2021)
The arylaluminum reagents are good nucleophiles for organic reactions because of their high reactivity, high chemoselective, low toxicity, and ease of preparation. Therefore, arylaluminum reagents are widely applied in many organic reactions. This review summarizes the recent advancement of the arylaluminum reagents applied in cross-coupling reactions, involving various reaction systems and properties of reaction.
Keywords: research progress